1978
DOI: 10.1161/01.cir.58.4.706
|View full text |Cite
|
Sign up to set email alerts
|

A new method for measurement of sinoatrial conduction time.

Abstract: This study describes a new method (NM) for estimation of sinoatrial conduction time (SACT), which utilizes constant atrial pacing (AP) instead of the premature atrial beats (PABs) used in the method reported in 1973 by Strauss et al. The SACTs were obtained by both methods in 20 patients. The SACT by the Strauss method (SM) was calculated as A2A3 minus A1A1. The NM consists of high right AP for a train of eight consecutive beats at rates less than or equal to 10 beats/min faster than the sinus rhythm. The inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0
2

Year Published

1983
1983
1991
1991

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 237 publications
(47 citation statements)
references
References 21 publications
0
45
0
2
Order By: Relevance
“…Sinus node depression ( + 80 to + 680 msec) was observed after pacing at cycle lengths of 700, 400, and 300 msec, whereas there was no change in sinus node automaticity after pacing at a cycle length of 500 msec. 30 Conventionally SNRT is measured from the last paced beat to the atrial electrogram in the region of the high right atrium. SNRT thus obtained was taken as a measure of sinus node automaticity.…”
Section: Resultsmentioning
confidence: 99%
“…Sinus node depression ( + 80 to + 680 msec) was observed after pacing at cycle lengths of 700, 400, and 300 msec, whereas there was no change in sinus node automaticity after pacing at a cycle length of 500 msec. 30 Conventionally SNRT is measured from the last paced beat to the atrial electrogram in the region of the high right atrium. SNRT thus obtained was taken as a measure of sinus node automaticity.…”
Section: Resultsmentioning
confidence: 99%
“…The pacemaker site was identified by extensive mapping of the endocardial sinus node area using 40-60 intracellular impalements as previously described.3 Dominant pacemaker fibers exhibit marked phase 4 depolarization, a smooth transition between phase 4 and phase 0 of the action potential, and the longest latency between activity of the cell and the atrium.…”
Section: Methodsmentioning
confidence: 99%
“…I Subsequent experimental studies have shown several inherent inadequacies of this technique.2 3 Using constant atrial pacing at rates slightly faster than sinus rhythm, Narula et al 4 found a simpler and quicker approach for measuring SACT. Data obtained by constant atrial pacing have been used to characterize sinus node function in man5-7 and also have been compared for validation with the results of independent method of direct extracellular direct-current recordings of sinus node activity.…”
mentioning
confidence: 99%
“…Developed tension was isometrically measured with a force displacement transducer (Nihon Kohden AP620G) connected to a part of the atrial muscle with a silk thread. Sinoatrial conduction time (SACT) was estimated using constant atrial pacing consisting of a train of 8 cycles at a rate 10 beats/min faster than the spontaneous rate (Narula et al, 1978). 6) Kobayashi et al7) reported that there was a good correlation between the SACT measured by the continuous atrial pacing method and by the premature atrial stimulation method (Strauss et al, 1973)8) using the isolated dog atrial preparation.…”
Section: -[3-(2-mentioning
confidence: 99%